2008
DOI: 10.21608/eajbsa.2008.15765
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastuctural changes in certain nymphal tissues of schistocerca gregaria (orthoptera: acrididae) by some chitin synthesis inhibitors.

Abstract: Ultrastuctural changes in certain nymphal tissues of schistocerca gregaria (orthoptera: acrididae) by some chitin synthesis inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…These histopathological changes by chlorfluazuron to great extent, agree with the results recorded for the same IGR on Musca domestica Bakr and Hussein (1988). In agreement with our obtained results, for some other IGRs on some insect species as Schistocerca gregaria Bakr et al, (2008), Lucilia cuprina Binnington et al, (1987).…”
Section: Susceptibility Testsupporting
confidence: 92%
“…These histopathological changes by chlorfluazuron to great extent, agree with the results recorded for the same IGR on Musca domestica Bakr and Hussein (1988). In agreement with our obtained results, for some other IGRs on some insect species as Schistocerca gregaria Bakr et al, (2008), Lucilia cuprina Binnington et al, (1987).…”
Section: Susceptibility Testsupporting
confidence: 92%
“…More importantly, it has been suggested that sublethal concentrations of pesticides can affect liver function by affecting energy metabolism [25]. Another study on related insecticides also identified ultrastructural changes in the mitochondria in last instar nymphs after treatment of the 1-day old penultimate instar nymphs of S. gregaria with 1000 ppm of Flufenoxuron or Lufenuron [39]. Therefore, it was necessary to study the biological effects of sublethal concentrations of buprofezin on energy metabolism modes in the liver to determine its potentially hepatotoxic effects.…”
Section: Discussionmentioning
confidence: 99%